OTC Hearing Aids: Pharmacy, Audiology, and Team-Based Approaches to Education and Practice Models - Steinkopf, Miranda (Seminars in Hearing, 2025)
Over-the-counter (OTC) hearing aids have the potential to greatly improve access to hearing health care in the United States. Though intended for self-care, health professionals should be at the forefront of determining service delivery models that will optimize the impact of OTC hearing aids. Collaborations between audiologists and pharmacists could be particularly successful due to pharmacists' high accessibility and audiologists' expertise in hearing health care. The two professions should continue to work together to help achieve optimum outcomes to best serve the public and their health. This will require education of both professions. Pharmacists now have continuing education opportunities to learn about OTC hearing aids.
Keywords: OTC hearing aids; audiology; pharmacy; education